Peran Religious Commitment dalam Hubungan Content Marketing terhadap Minat Beli Kuliner Gen Z Muslim Kota Jambi di TikTok - Puspita Sari; Lucky Enggrani Fitri; Try Syeftiani; Syahmardi Yacob (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of Content Marketing on culinary buying interest in Gen Z Muslims in Jambi City with Religious Commitment as an intervening variable. This study is important because it shows how digital marketing strategies not only play a role in attracting consumers, but also interacting with the religious values held by Muslim communities. The research uses a quantitative approach with an explanatory research method. Data was obtained through the distribution of questionnaires to 96 Gen Z Muslim respondents who actively use TikTok, then analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique with the help of SmartPLS 4.0 software. The results of the study show that Content Marketing has a positive and significant effect on Buying Interest and Religious Commitment. However, Religious Commitment has a negative effect on Buying Interest, thus mediating the relationship between Content Marketing and Buying Interest negatively. These findings confirm that the higher the level of religious commitment a consumer, the more cautious he or she is in responding to culinary marketing content. Thus, culinary business actors need to ensure that the Content Marketing strategy presented is not only visually appealing, but also emphasizes the halal-thayyib aspect to be in harmony with the religious values of Muslim consumers